PEMANFAATAN LIMBAH CANGKANG RAJUNGAN MENJADI KITIN DAN KITOSAN PADA UMKM RAJUNGAN KUPAS KOTA LANGSA - Seprianto, Seprianto; Alham, Fiddini; Mahyuny, Siska Rita; Komariyah, Siti (Universitas Mataram, 2025)
Kuala Langsa Village, located in the city of Langsa, is a coastal area where the majority of the population works as fishermen, primarily catching blue swimming crabs. The local MSME (Micro, Small, and Medium Enterprise), UD Langsa Jaya, produces a significant amount of crab shell waste, which has so far been discarded into the sea. This waste can actually be processed to produce chitin and chitosan—both of which are valuable and environmentally friendly materials. However, the partner lacks the knowledge, skills, and tools necessary to manage this waste effectively. The objective of this program is to enhance the partner's knowledge and skills in processing crab shell waste into chitin and chitosan, which are both economically valuable and eco-friendly products. The methods used in this program include planning, preparation, implementation, and monitoring and evaluation. Additionally, the activities involve identifying the partner's problems, socializing the benefits of crab shell waste utilization, conducting training on chitin and chitosan production, and carrying out continuous evaluations of each stage. At UD Langsa Jaya, the training successfully taught five female workers how to transform crab shell waste into chitin and chitosan. They learned about waste processing and the economic and environmental benefits of the resulting products. This training not only improved the participants' skills but also helped reduce marine pollution. The use of chitosan as a natural preservative can also lower production costs for UD Langsa Jaya and make its products more competitive. Overall, this activity enhanced the partner’s knowledge and skills in processing crab shell waste into chitin and chitosan that are both economically valuable and environmentally sustainable.